Mangrove Honey Bees: A Food and Nutrition Security Solution for Coastal Communities Affected by Climate - Retno Hestiningsih; Moh Arie Wuryanto; Sri Yuliawati; Henry Setiawan; Dwi Sutiningsih; Meira Nur Aini; Martini Martini (Jurnal Abdimas, 2026)
Climate change has caused significant impacts on coastal areas, particularly in the form of tidal flooding, coastal abrasion, and environmental degradation, which in turn affect food and nutrition security as well as the socio-economic conditions of local communities. This community service activity aimed to strengthen food and nutrition security while enhancing the adaptive capacity of coastal communities to climate change through the sustainable utilization of mangrove ecosystems by implementing mangrove honey bee cultivation in Tugu District, Semarang City. The program employed a participatory community-based approach that included socialization activities, a one-day technical training on mangrove honey bee cultivation, the establishment of a community business group, and the assessment of participants’ knowledge improvement using pretest and posttest methods. The results indicated an increase in participants’ knowledge following the training, accompanied by improved community awareness regarding the importance of mangrove conservation and the economic potential of mangrove honey as a nutritious food source. Furthermore, the program successfully facilitated the formation of a mangrove honey bee management group oriented toward sustainable business development. Based on these findings, it can be concluded that mangrove honey bee cultivation has strong potential as an effective climate change adaptation strategy to support food and nutrition security as well as the economic resilience of coastal communities. The recommendations emphasize the need for continuous mentoring, strengthening of community business institutions, and the integration of mangrove conservation programs with local economic development to support the implementation of nature-based community service models in coastal areas.